Fluorescent Anemones in Japan–Comprehensive Revision of Japanese Actinernoidea (Cnidaria: Anthozoa: Actiniaria: Anenthemonae) with Rearrangements of the Classification - Izumi, T.; Fujii, T.; Yanagi, K.; Fujita, T. (Diversity, 2023)
Actinernoidea is a superfamily of the suborder Anenthemonae of the order Actiniaria, subclass Hexacorallia. This superfamily has been diagnosed by a peculiar endocoeletic mesenterial arrangement and included two families, Actinernidae and Halcuriidae. Although the monophyly of this superfamily is anticipated based on preceding molecular phylogenetic works, the relation-ship between these two families was not certain because of the rarity of actinernoidean anemones. We conducted comprehensive sampling in Japan, where the highest diversity of actinernoideans is known, and conducted phylogenetic analyses using nuclear and mitochondrial gene markers. Ac-cording to the comprehensive analyses, both Actinernidae and Halcuriidae were not indicated as monophyletic but rather as poly- or paraphyletic. Based on our phylogeny reconstruction, we pro-pose a new classification for Actinernoidea composed of three families, including Isactinernidae fam. nov., and seven genera, including Isohalcurias gen. nov. We also describe four new species, Halcurias hiroomii sp. nov., H. fragum sp. nov., Isohalcurias citreum sp. nov., and I. malum sp. nov.; and propose a new combination, Isohalcurias carlgreni comb. nov. This work is the first study of Actinernoidea that comprehensively analyzes its phylogeny and rearranges its classification, showing that there is highly divergent fauna in the seas around Japan.